2020
DOI: 10.4102/sajid.v35i1.174
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate for the treatment of severe malaria: A retrospective review of patients admitted to two tertiary hospital intensive care units in Johannesburg, South Africa

Abstract: BackgroundAccording to the 2013 World Health Organization (WHO) World Malaria Report, malaria is a major cause of mortality and morbidity in malaria-endemic areas of the world. In 2018, 228 million cases of malaria were estimated to have been reported throughout the world with 85% of cases in sub-Saharan Africa and India. 1 This makes malaria the second most common cause of infectious disease-related deaths in the world, after tuberculosis. 2 Malaria is prevalent throughout most of the tropical regions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…No controlled clinical trials have been conducted to examine the efficacy of artesunate in the management of HHV infections 31 . However, clinical case reports have shown an encouraging outlook for this medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No controlled clinical trials have been conducted to examine the efficacy of artesunate in the management of HHV infections 31 . However, clinical case reports have shown an encouraging outlook for this medication.…”
Section: Discussionmentioning
confidence: 99%
“…No controlled clinical trials have been conducted to examine the efficacy of artesunate in the management of HHV infections. 31 However, clinical case reports have shown an encouraging outlook for this medication. Thus, Sellar et al reported the effectiveness of using artesunate for treating reactivated intractable HSV1/2 strain, which is multiresistant to acyclic nucleoside analogs, in patients who underwent allogeneic bone marrow transplantation.…”
Section: Discussionmentioning
confidence: 99%